2013
DOI: 10.1371/journal.pone.0059219
|View full text |Cite|
|
Sign up to set email alerts
|

Bioengineered 3D Human Kidney Tissue, a Platform for the Determination of Nephrotoxicity

Abstract: The staggering cost of bringing a drug to market coupled with the extremely high failure rate of prospective compounds in early phase clinical trials due to unexpected human toxicity makes it imperative that more relevant human models be developed to better predict drug toxicity. Drug–induced nephrotoxicity remains especially difficult to predict in both pre-clinical and clinical settings and is often undetected until patient hospitalization. Current pre-clinical methods of determining renal toxicity include 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 44 publications
2
116
0
Order By: Relevance
“…In one case, isolation of a specific clone was required to facilitate cyst formation in collagen gels (36). Therefore, to use the LLC-PK1 cell line to consistently induce cyst growth in 3D, we used a hormonal media composition previously shown to produce structural growth of immortalized human renal proximal tubule cells and primary human cortical cells in 3D tissues (37,38). In addition, hormone-supplemented media has historically been used to support LLC-PK1 growth (39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one case, isolation of a specific clone was required to facilitate cyst formation in collagen gels (36). Therefore, to use the LLC-PK1 cell line to consistently induce cyst growth in 3D, we used a hormonal media composition previously shown to produce structural growth of immortalized human renal proximal tubule cells and primary human cortical cells in 3D tissues (37,38). In addition, hormone-supplemented media has historically been used to support LLC-PK1 growth (39).…”
Section: Resultsmentioning
confidence: 99%
“…For 3D tissues, cells were embedded in a previously described mixture of Matrigel and type I collagen (37). Cystic structures were monitored for size by both H&E staining and whole-tissue staining of tissues after 2, 4, 6, and 8 wk of culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have revealed advantages of 3D tissue models over 2D cell cultures due to differences in cell-cell signaling, ECM interactions, ECM composition, gene expression, and epigenetic gene regulation (23,36). Bioengineered 3D kidney tissues produced in our lab using human cells have been shown to better reflect human renal physiology than 2D cell culture (37). These tissues are composed of human telomerase reverse transcriptase (hTERT) immortalized human renal proximal tubule cells embedded within a hydrogel.…”
mentioning
confidence: 99%
“…This transformation allows the cells to maintain their intact chromosomes after every doubling, resulting in stable lines [70][71][72].…”
Section: Conditionally Immortalized Cell Linesmentioning
confidence: 99%